(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2018)
In this article we propose to share some of the tours of the investigation "The borders of the families. An exercise of looks at the international adoption from the anthropologic strangeness and feminist" that will be presented by Noemí González Carballés in the next months, in the Program of Doctorate in "Studies of the Women. Speeches and practices of Gender" of the University of Granada, for the obtaining of the doctor’s degree and that has been directed by another signatory authoress of this work. It has seemed to us to be interesting to exhibit in this brief space, how there arise the questions of this investigation and how they drive us to reread ethnographies and historical works, to realize finally our analytical offer of the international adoptions, from Anthropology of the public policies (Shore and Wright, 1997).